Le courant du Labrador et quelques-unes de ses conséquences géographiques - Biays, Pierre (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1960)
I. A part of the West Greenland current flows westwards across the Davis Strait and meets the Canadian (Baffin Land) current to form the Labrador current which follows southwards the shelf and slope of Labrador Coast {figure I). Meeting the northern edge of the Newfoundland Banks, the Labrador current splits in a minor western branch running along the Avalon Peninsula and a major one proceeding south along the eastern edge of the shelf down to the Tail of the Grand Banks. There it meets the Atlantic current which very often forms a prominent westward salient at about 45°N. and 47 - 48°W. (figure IX). This salient tends to deflect and turn back east or northeastwards a variable portion of the major branch. The turning point and the volume of the deflected stream are subject to change according to the position and importance of the Atlantic salient. It is estimated that the West Greenland current and the Canadian current join respectively in a 60% and 40% ratio. The major eastern branch in the Grand Banks region amounts to 80 to 90%, splitting in turn about fifty-fifty in an eastward stream flowing just north of Flemish Cap and the current proceeding southwards along the edge of the Grand Banks.One of the most striking features of the Labrador current is its banded structure. In the area where it forms there are at least three bands (figure VII) : 1. a fresh and very cold inshore band made of polar and coastal waters ; 2. an offshore stream in the Canadian current carrying Baffin Bay waters ; and, 3. — further seawards — the West Greenland portion whose waters are mild in temperature and possess Atlantic salinity. Two cold walls mark the sharp limits between these bodies of water. Along the Labrador Coast the banding agrees pretty well with the submarine topography ; an inshore slow, cold and fresh stream is confined to the continental shelf while an offshore fast, mild and salted current follows the edge of the shelf and slope. Both exhibit shoreward and seaward salients in agreement to the shelf varying in width.In the Grand Banks area — apart from the well known Newfoundland cold wall between the contrary Labrador and Atlantic currents (see figure XII, A) — there is a marked cold wall inside the eastwards proceeding current between the bulk of the Atlantic waters and that part of Labrador waters that have been deflected by the Atlantic salient and incorporated to the eastward drift (see figures X and XIII). The point of annual cycle and long term temperature and volume variations is not discussed here in full.Some words are devoted to the vernal warming and the maintaining jar into the summer of cold waters on the central part of the Grand Banks (figure XIV).II. Three kinds of sea ice occur along the Labrador Coast and the Atlantic Coast of Newfoundland : 1. the bay or winter ice ; 2. the drift ice ; 3. the icebergs. The bay or winter ice forms every winter and disappears during spring time. The inner parts of the bays of Northern Labrador are frozen over by the middle of December while the offshore inlets and archipelagos are jammed much later, say in the course of January. A tentative map has been sketched to show the date of occurrence of the winter ice. Ice grows till it reaches a width of between 10 and 40 miles, but its thickness never exceeds three feet or so. The bay ice is subject to break during stormy weather and therefore is able to feed largely the drift ice in the heart of winter.Drift ice is made up of both local winter ice and — mainly in the first summer months —• old arctic ice. Due to age and hummockying processes the latter is characterized by heavy pieces and floes which often reach a thickness of 30 to 50 feet. Although the main track of the drift ice is governed by the Labrador current the actual short-range movements are controlled by the changing wind conditions. Four examples of drifting fields are reported. Wind control is pretty well illustrated by sketch-maps XVIII and XIX which show the appearance, deterioration and receding of ice fields carried by the Labrador current in the vicinity of Newfoundland's northern and eastern coasts. The disappearance of an ice field drifting off Southern Labrador and blocking the eastern entrance to the Strait of Belle-Isle — as shown on figure XX — is typical of the features marking the end of the ice season. Figure XXI represents heavy arctic pieces and drift ice of local origin closely packed in the central arc of the Labrador Coast before being swept away by land-breeze. Because of these changing conditions it seems difficult to de fine an average annual cycle of drift ice. The maximum limits are reached by the middle of April ; at that time ice extends as jar south as the 47 th or the 46 th parallel, but normally it keeps off the coast south of St. John s, this harbour being very seldom closed to navigation for more than ten successive days. Tentative is made to show in sketch-maps the average conditions in winter (figure XVI) as well as the receding of the drifting fields and tongues during spring and summer months (figure XVII).The story of the bergs from the parent glaciers of West Greenland down to their melting place around the Banks begins to be a well known one (see figure XXII). According to their very deep draft the bergs are less subject than the drift ice to be driven by the surface and subsurface wind wurrents. Mortality in Baffin Bay, melting and grounding on the Labrador Coast, differential velocity of inshore and offshore bands of the current, location of the point of partition between the eastern and western branches are discussed in order to explain the observed distribution of bergs in the Grand Banks region, jour typical patterns of which are shown on figure XXIII.III. An attempt has been made to show the division between ice and navigation at selected places along the coasts watered by the Labrador current. Figure XXIV is only tentative since the actual conditions due to changing weather often differ strongly from the average ones. When possible, drift ice season has been distinguished. The relatively favoured position of the St. John's harbour appears both on figure XXIV and figures XVI and XVIII. Along the Labrador Coast and in the northern part of the island of Newfoundland, dog sleigh is often the only means of transportation in winter, when fiat bay ice is wide enough and has not been hummockied or broken by stormy weather. Main sleigh tracks and their alternatives are governed by physical conditions as well as winter settlement pattern and therefore are seldom subject to change. Examples of sleigh tracks have been taken in Northern and Central Labrador (figures XXV and XXVI).In the populated areas of Northeastern Newfoundland where fast access to markets and mass transportation are needed, sleighing in winter is no more possible. It can be said that these economic conditions are the main stimulus forroad building in the island. More and more « outports » are progressively freed from backward means of transportation and yin summertime yfrom the navigation itself too. The closing of navigation in the Bay of Exploits (the innermost part of Notre Dame Bay) results in the railway between the said bay and St. John s being peculiarly overloaded in winter, since paper from Bishop's Falls and ore concentrates from Buchans can no more be shipped through Botwood on the Bay of Exploits {figure XXVII).